Choosing Teaching as a Career: Altruistic, Intrinsic, and Extrinsic Motives - Repblicha Astriyadi (Jurnal Sinar Edukasi, 2021)
Teaching is a noble profession and has helped to shape many nations. Governments around the world recognize that quality teachers and teaching are central to the development and maintenance of an intelligent, informed people. This paper discusses about three broad categories of motives for choosing teaching as a career: intrinsic, extrinsic, and altruistic reasons. Altruistic reasons deal with the factors beyond the job itself, seeing teaching as a socially worthwhile and important job and a desire to help society improve. Intrinsic reasons cover aspects of the job activity itself, such as the activity of teaching children, and an interest in using their subject matter knowledge and expertise. Extrinsic reasons can be defined as the benefits and perks offered such as long holidays, level of pay, and status.